Balbuk Haus / Nur Jasmine Athirah Azhar … [et al.] - Azhar, Nur Jasmine Athirah; Ahmad Fikri, Nur Alia Farhanna; Shahrizal, Nur Shafiqah Shazwani; Muhammad Farid, Izzah Atirah (2022)
Balbuk Haus is a sole proprietorship business located in Kangar, Perlis. It has been operating since May 2022 and serves traditional Perlis food, coffee and air bunga telang. The objective is to satisfy customer product requests and give the highest quality at the most competitive pricing. They also provide outstanding and respectful customer service and are active on social media. They have been certified as Halal by Jabatan Kemajuan Islam Malaysia (JAKIM) and offer traditional Perlis food at an affordable price, with prices ranging from RM5.00 to RM12.00. An operational strategy is a plan that governs an organization's resource allocation and utilizes it to maintain a competitive edge. Operational strategy is a decision-making process that affects an organization's long-term plan for achieving the goals of the mission statement. Balbuk Haus Cafe is outsourcing to other logistic industries to ensure fresh products and improve market share. Financial achievement is an unreliable measure of a company's ability to earn money. Balbuk Haus has poor product packaging, lack of main power, and a less customer-friendly environment. To improve customer satisfaction and increase product demand, the company must improve product packaging, recruit main power workers, apply customer family friendly places, provide customers with a variety of payment options, give customers a Google form or comment card, and develop bottle caps that are tighter and less likely to leak during delivery.